The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/microorganisms11112640
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Lymphopenia in Severe Tuberculosis

Fei Li,
Dandan Chen,
Qingqing Zeng
et al.

Abstract: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis (M. tuberculosis). In lymphopenia, T cells are typically characterized by progressive loss and a decrease in their count results. Lymphopenia can hinder immune responses and lead to systemic immunosuppression, which is strongly associated with mortality. Lymphopenia is a significant immunological abnormality in the majority of patients with severe and advanced TB, and its severity is linked to disease outcomes. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 121 publications
0
0
0
Order By: Relevance
“…3 D). The increased activity observed in C3 suggests an augmented demand for blood cells throughout the disease process, driven by heightened immune responses and inflammation, which potentially leads to escalated blood cell consumption and demand 30 . Additionally, the closely intertwined relationship between reactive oxygen species (ROS) and oxidative stress pathways with macrophages in tuberculosis underscores the pivotal role of these pathways in combating PTB infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 D). The increased activity observed in C3 suggests an augmented demand for blood cells throughout the disease process, driven by heightened immune responses and inflammation, which potentially leads to escalated blood cell consumption and demand 30 . Additionally, the closely intertwined relationship between reactive oxygen species (ROS) and oxidative stress pathways with macrophages in tuberculosis underscores the pivotal role of these pathways in combating PTB infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar mechanism was postulated to be correlated with the reallocation of T lymphocytes in the tissues [ 42 ]. Besides that, M. tuberculosis-induced T lymphocyte apoptosis, hematopoietic dysfunction, and T-cell exhaustion [ 43 ]. While malaria-associated lymphopenia was described to be mainly due to Fas-induced apoptosis [ 44 ], other studies reported no detected apoptosis in the peripheral blood mononuclear cells (PBMCs) [ 45 ].…”
Section: Lymphopeniamentioning
confidence: 99%
“…The correlation between lymphocyte count and TB is a subject of debate. Some researchers report lymphopenia as a prominent feature, especially in severe disease [15], while others note lymphocytosis [16]. Neutrophils and macrophages play a critical role in the initial immune response (innate immunity) against TB by forming granulomas [17].…”
Section: Introductionmentioning
confidence: 99%